KAMPANYE EDUKASI PENCEGAHAN BULLYING DAN HATE SPEECH PADA SMA SWASTA YPWI KOTA JAMBI - Mulyadi Mulyadi; Muspawi Muspawi; Yudo Handoko; Sundari Utami (LPPM Universitas Bina Bangsa, 2023)
Cases of bullying and hate speech in Indonesia topped the ranking. Bullying and hate speech often occur when someone has shortcomings in themselves, both physically and mentally. The impact of bullying and hate speech for students is in the form of decreased appetite, headaches, embarrassment, and feeling afraid to hang out in social environments. Increasing students' understanding of bullying and hate speech behavior can reduce cases of bullying and hate speech. Service activities are carried out at SMAS YPWI Jambi City. This activity is carried out with the aim of providing understanding and increasing knowledge of adolescents about bullying and hate speech behavior and the consequences of psychological impacts. The method of implementing this activity is by means of counseling designed in the form of material presentation as well as discussion and question and answer. Through this activity students gain knowledge about bullying and hate speech, know the forms and factors that influence bullying and hate speech, types of bullying and hate speech, and how to fight bullying and hate speech so as not to cause adverse effects on psychic conditions. The benefits of implementing this activity for schools are the awareness of the school on the adverse effects of bullying and hate speech behavior so that they can carry out various policies to reduce and prevent cases of bullying and hate speech in schools